AN ERROR ANALYSIS OF STUDENTS’ RECOUNT TEXT ON SIMPLE PAST TENSE AT THE EIGHTH GRADE OF SMP NEGERI 4 GUNUNGSITOLI UTARA - Afore Tahir Harefa (Jurnal Review Pendidikan dan Pengajaran (JRPP), 2018)
The researcher conducted qualitative research used descriptive qualitative method. The researcher concluded that the types of error that were made by the students of the second year of SMP Negeri 4 Gunungsitoli Utara in their English writing from the highest frequency and percentage to the lowest are: error of misformation 257 (67%), omission 60 (16%), misordering 49 (13%) and addition 20 (5%). Meanwhile, the source of students error from the highest frequency and percentage to the lowest are interlingual 44 (44%), intralingual 43 (43%), context of learning 8 (8%) and communication strategy 5 (5%). In other words, most of the students were still influenced by their Indonesian language thinking. Besides, errors occurred because the students generalized the rule and applied it incompletely. Then, the errors occurred because of the the teacher explanation and the errors also occurred because of the students’ learning techniques. Based on the result, the usage of simple past tense in writing recount text is difficult for the students. Then, the researcher also suggests the other researchers to do the research in the future because analysis research gives the evidence and support the next action.